Phytochemical and Metabolomic Investigation of a Popular Traditional Plant from La Réunion: Psiloxylon mauritianum - Théo Ozga; Gaëtan Herbette; Patrick Carriere Richez; Patricia Clerc; Juliano Haddad; Chaker El Kalamouni; Jérôme Bignon; Rémy Marcellin-Gros; Emerson Ferreira Queiroz; Jean-Luc Wolfender; Jacqueline Smadja; Anne Gauvin-Bialecki (Applied Sciences)
A molecular network investigation of Psiloxylon mauritianum leaf extracts from five different specimens led to the detection of a diversity of flavonoids, triterpenes, and phloroglucinols. Some compounds from these molecular classes are reported to target fever-linked symptoms (antioxidant, antiviral, anti-inflammatory, and antibacterial activities) and may explain the plant’s success as a local traditional remedy. The phytochemical study of one extract allowed the isolation and characterization of an original seco-ring-A lupane structurally similar to the anti-inflammatory betulinic acid, 11 known triterpenes, 2 flavonoids, and a chalcone. Antiviral assays highlighted the in vitro anti-Zika activity of corosolic and betulinic acids found in the plant. Some interesting structure–activity relationships could be drawn between the new compound and the known active triterpenes.